Photocatalytic C−C Bond Cleavage and Amination of Cycloalkanols by Cerium(III) Chloride Complex. Issue 49 (11th November 2016) - Guo, Jing‐Jing; Hu, Anhua; Chen, Yilin; Sun, Jianfeng; Tang, Haoming; Zuo, Zhiwei
Abstract: A general strategy for the cleavage and amination of C−C bonds of cycloalkanols has been achieved through visible‐light‐induced photoredox catalysis utilizing a cerium(III) chloride complex. This operationally simple methodology has been successfully applied to a wide array of unstrained cyclic alcohols, and represents the first example of catalytic C−C bond cleavage and functionalization of unstrained secondary cycloalkanols. Abstract : Breaking (D)BAD : A general strategy for the cleavage and amination of C−C bonds of cycloalkanols has been achieved through visible‐light‐induced photoredox catalysis utilizing a cerium(III) chloride complex. This method represents the first example of catalytic C−C bond cleavage and functionalization of unstrained secondary cycloalkanols. DBAD=di‐ tert ‐butyl azodicarboxylate, Boc= tert ‐butoxycarbonyl.